Measuring Service Quality in the Travel and Tourism Industry in Nepal - Shahi, Puja (Nepalese Journal of Economics, 2025)
This study examines measuring service quality in travel and tourism in Nepal. Customer satisfaction is the dependent variable. The selected independent variables are staff training, infrastructure, customer feedback mechanism, cultural sensitivity, and service innovation. The primary source of data is used to assess the opinions of respondents regarding staff training, infrastructure, customer feedback mechanism, cultural sensitivity, service innovation, and customer satisfaction. The study is based on primary data of 119 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of service quality in travel and tourism in Nepal. The study shows that staff training is positively correlated to customer satisfaction indicating that higher the staff training, higher will would be the customer satisfaction. Likewise, infrastructure are positively correlated to the customer satisfaction indicating that higher the infrastructure, higher will would be the customer satisfaction. Similarly, customer feedback mechanism is positively correlated to customer satisfaction indicating that better customer feedback mechanism lead to increase in customer satisfaction. Furthermore, cultural sensitivity is positively correlated to customer satisfaction. This implies supportive cultural sensitivity leads to increase in customer satisfaction. However, service innovation is positively correlated to the improvement customer satisfaction. It shows that proper service innovation leads to improve in tourism of Nepal.